1995
DOI: 10.1096/fasebj.9.1.7821763
|View full text |Cite
|
Sign up to set email alerts
|

Preferential expression of CD30 by human CD4 + T cells producing Th2‐type cytokines

Abstract: A large panel of human CD4+ T helper (Th) cell clones with established Th1, Th2, or Th0 profiles of cytokine secretion were examined for the expression of CD30, a member of the tumor necrosis factor receptor superfamily. Th1 clones expressed poor or no CD30 mRNA, and showed low or undetectable expression of both membrane and soluble CD30 (sCD30) protein, whereas Th2 clones showed both CD30 mRNA and membrane CD30 and released substantial amounts of sCD30, Th0 clones exhibited an intermediate pattern of CD30 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
233
1
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(249 citation statements)
references
References 0 publications
13
233
1
2
Order By: Relevance
“…Previous in vitro findings demonstrated that HIV replication mainly occurs within CD4 + cells of Th2 and Th0-type [13], which preferentially express and release CD30 [4,10], and that HIV infection up-regulates CD30 cell expression and release [4,6]. In the light of the above observations, the elevated circulating levels of sCD30 during acute infection and their positive correlation with serum concentration of HIV antigen suggest the possibility that they reflect the high rate of in vivo occurring viral replication.…”
Section: Discussionmentioning
confidence: 89%
“…Previous in vitro findings demonstrated that HIV replication mainly occurs within CD4 + cells of Th2 and Th0-type [13], which preferentially express and release CD30 [4,10], and that HIV infection up-regulates CD30 cell expression and release [4,6]. In the light of the above observations, the elevated circulating levels of sCD30 during acute infection and their positive correlation with serum concentration of HIV antigen suggest the possibility that they reflect the high rate of in vivo occurring viral replication.…”
Section: Discussionmentioning
confidence: 89%
“…[1][2][3][4] CD30, CD40, OX40, and CD95 at least have been involved in lymphoid differentiation and effector functions. 5 CD30, originally described as a marker of a number of lymphoma cells and reactive lymphoblasts, 6 is expressed by activated and memory T cells, [6][7][8][9] medullary thymocytes, 10,11 B cells, natural killer cells, and some nonhematologic cells. 12 Its expression by T cells is essentially dependent on activation involving IL-4 and CD28 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…12 Its expression by T cells is essentially dependent on activation involving IL-4 and CD28 signaling. 9,13 The IL-4 requirement is probably the reason for the association of CD30 expression with preferential Th0-and Th2-type immune responses in vitro 8 and in vivo. [14][15][16] Stimulation of CD30 by CD153 (CD30 ligand) leads to nuclear mobilization of NF-B complexes 17 while inducing a signal-coupled depletion of TRAF2, which increases the cell sensitivity to TNFR1-dependent apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD30L-CD30 interaction, like TNF-R and CD95, is likely to be involved in cell death signaling and participates in negative selection of thymic T lymphocytes. In contrast, both CD30 and CD30L can be expressed by activated T cells, and the CD30-mediated signaling enhances proliferation and cytokine secretion by Th2 cells, and probably by Th1 and Th0 cells (Del Prete et al, 1995;Hamann et al, 1996;Mingari et al, 1996). For B cells, CD30L can stimulate its proliferation, antibody production, and secretion in a cytokine (eg, IL-4 and IL-5)-dependent manner (Shanebeck et al, 1995).…”
Section: Table 1 Expression Of Cd30 and Cd30l In Cultured Cellsmentioning
confidence: 99%